Whole Genome Sequencing Shows a Low Proportion of Tuberculosis Disease Is Attributable to Known Close Contacts in Rural Malawi. - Judith R Glynn; José Afonso Guerra-Assunção; Rein M G J Houben; Lifted Sichali; Themba Mzembe; Lorrain K Mwaungulu; J Nimrod Mwaungulu; Ruth McNerney; Palwasha Khan; Julian Parkhill; Amelia C Crampin; Taane G Clark (PLoS ONE)
Background The proportion of tuberculosis attributable to transmission from close contacts is not well known. Comparison of the genome of strains from index patients and prior contacts allows transmission to be confirmed or excluded. Methods In Karonga District, Malawi, all tuberculosis patients are asked about prior contact with others with tuberculosis. All available strains from culture-positive patients were sequenced. Up to 10 single nucleotide polymorphisms between index patients and their prior contacts were allowed for confirmation, and ≥ 100 for exclusion. The population attributable fraction was estimated from the proportion of confirmed transmissions and the proportion of patients with contacts. Results From 1997-2010 there were 1907 new culture-confirmed tuberculosis patients, of whom 32% reported at least one family contact and an additional 11% had at least one other contact; 60% of contacts had smear-positive disease. Among case-contact pairs with sequences available, transmission was confirmed from 38% (62/163) smear-positive prior contacts and 0/17 smear-negative prior contacts. Confirmed transmission was more common in those related to the prior contact (42.4%, 56/132) than in non-relatives (19.4%, 6/31, p = 0.02), and in those with more intense contact, to younger index cases, and in more recent years. The proportion of tuberculosis attributable to known contacts was estimated to be 9.4% overall. Conclusions In this population known contacts only explained a small proportion of tuberculosis cases. Even those with a prior family contact with smear positive tuberculosis were more likely to have acquired their infection elsewhere.